Perencanaan Pemasaran Jasa Pendidikan di SMP IT Mufidatul Ilmi Kabupaten Banyuasin - Ibrahim Ibrahim; Mardiah Astuti; Syafrina Hana Aulia (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to understand the Marketing Planning of Educational Services at SMP IT Mufidatul Ilmi Banyuasin. The research is a qualitative descriptive study, with 6 research subjects, including the school principal, curriculum vice-principal, administrative head, educators, parents, and students. Data is collected through three methods: interviews, observations, and documentation. Subsequently, the data analysis technique begins with data collection, data presentation, and data verification. The research results indicate that: (1) Goal Setting involves holding meetings twice a year in January and June and establishing a special committee for student admissions. (2) Formulating Current Conditions is based on the school's profile, vision, the number of educators, educational quality, and infrastructure conditions, which are formulated through meetings for effective implementation. (3) Identifying Facilities and Barriers through SWOT Analysis has been conducted effectively through meetings. (4) Plan Development is carried out effectively by the school principal, curriculum vice principal, teachers, and staff with direct coordination and evaluation of the previous plans